Silica supported barium chloride (SiO2-BaCl2): efficient and heterogeneous catalyst for the environmentally friendly preparation of N,N'-alkylidene bisamides under solvent-free condition - Shafiee, Mohammad Reza Mohammad; Zakaria, Mohamad Pauzi; Azar, Parviz Aberomand (IEEE, 2010)
A series of N,N'-alkylidene bisamides were prepared via a green and environmentally friendly synthetic protocol from the reaction of phenyl acetylene/1-Hexyne, aromatic aldehyde and benzamide/acetamide. Silica Supported Barium Chloride (SiO2-BaCl2) catalyzes the reaction. The prepared catalysts were characterized by X-ray diffraction. The products were obtained with high conversion and yields.